2010
DOI: 10.1590/s0100-83582010000400005
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do potencial alelopático de substâncias isoladas em sementes de araticum (Annona crassiflora)

Abstract: RESUMO -Este estudo visou identificar substâncias biologicamente ativas e o potencial alelopático de esteroides glicosilados, provenientes das sementes de Annona crassiflora. O isolamento dos esteroides glicosilados foi realizado com a separação dos constituintes químicos do extrato bruto de acetato de etila em coluna cromatográfica, sendo a completa elucidação estrutural por meio de espectroscopia de RMN ABSTRACT -This work aimed to identify substances and the allelopathic potential of steroidal glycosides, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 16 publications
1
5
0
1
Order By: Relevance
“…These results are in agreement with the finding that extracts of allelopathic plants generally have more pronounced effects on radicle rather than hypocotyl growth (Inoue et al, 2010;Grisi et al, 2012). Root growth is characterized by high metabolic rates, and for this reason roots are highly susceptible to environmental stresses, such as allelochemicals in substrate (Cruz-Ortega et al, 1998).…”
Section: Effect Of Serjania Lethalis Ethanolic Extract On Weed Controlsupporting
confidence: 87%
See 2 more Smart Citations
“…These results are in agreement with the finding that extracts of allelopathic plants generally have more pronounced effects on radicle rather than hypocotyl growth (Inoue et al, 2010;Grisi et al, 2012). Root growth is characterized by high metabolic rates, and for this reason roots are highly susceptible to environmental stresses, such as allelochemicals in substrate (Cruz-Ortega et al, 1998).…”
Section: Effect Of Serjania Lethalis Ethanolic Extract On Weed Controlsupporting
confidence: 87%
“…The effects of hydroalcoholic extracts of Annona crassiflora leaves and stems on the germinability and mean germination rate of wild poinsettia seeds were similar, but the stem extracts more strongly inhibited shoot and root growth than did the leaf extracts (Inoue et al, 2010). Li & Jin (2010) also reported that the stem extracts of Mikania micrantha showed higher inhibitory activity than the leaf extracts.…”
Section: Effect Of Serjania Lethalis Ethanolic Extract On Weed Controlmentioning
confidence: 94%
See 1 more Smart Citation
“…. Th e root system was more sensitive to allelochemicals than shoot seedling Root sensitivity to allelochemicals is well documented in the literature, as it is one of the characteristics that best indicates the phytotoxicity of plant extracts (Inoue et al 2010;Souza et al 2010;Grisi et al 2012). Th is can be attributed to the fact that root growth is characterized by high metabolic rates and the roots are therefore highly susceptible to environmental stress, such as allelochemicals in the substrate (Cruz-Ortega et al 1 998).…”
Section: Resultsmentioning
confidence: 99%
“…Vários aleloquímicos foram descritos de diferentes espécies de plantas, sendo alguns exemplos os benzoxazinoides, as benzoquinonas, os glucosinolatos e os terpenos (Jabran, 2017 (Inoue et al, 2010b).…”
Section: Introductionunclassified